2013
DOI: 10.1007/s11255-013-0595-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effect of renal cell carcinoma on phenotype and function of dendritic cells

Abstract: Dendritic cells (DCs) play an important role in anti-renal cell carcinoma (RCC) immunity. The aim of the study was to investigate effect of mimic RCC microenvironment on phenotype and function of DCs. We isolated conditioned media (CM) from supernatants of culturing RCC cells and adjacent non-RCC cells in patients. CD14+ monocytes were obtained from healthy donors. The monocytes derived DCs were treated by RCC CM and non-RCC CM. Maturation markers CD80, CD83, CD86, and HLA-DR on DCs were analyzed using flow cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…Accordingly, several studies have shown that the ccRCC microenvironment can induce a dysfunctional DC maturation, a downregulation of costimulatory molecules and tolerogenicity (34,41,42), whereas DC in the TLS are likely to be protected from these effects (43). Altogether, our results suggest that the particular proinflammatory milieu initiated by tumor cells induces the recruitment of CD8 þ T cells that-due to the low number of fully functional mature DC present in specialized Tcell-priming sites, or the presence of DC with suppressive phenotype-are not able to mount an effective antitumor immune response, but rather express exhaustion/inhibition molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, several studies have shown that the ccRCC microenvironment can induce a dysfunctional DC maturation, a downregulation of costimulatory molecules and tolerogenicity (34,41,42), whereas DC in the TLS are likely to be protected from these effects (43). Altogether, our results suggest that the particular proinflammatory milieu initiated by tumor cells induces the recruitment of CD8 þ T cells that-due to the low number of fully functional mature DC present in specialized Tcell-priming sites, or the presence of DC with suppressive phenotype-are not able to mount an effective antitumor immune response, but rather express exhaustion/inhibition molecules.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence suggests that RCC microenvironment is enriched in molecules that hamper DC activity and maturation, since their phenotypic abnormalities are restricted to cells embedded in the tumor stroma and can be reversed when they are removed from the tumor. In addition, conditioned media from RCC primary cultures or cell lines can induce in vitro tolerogenic and dysfunctional DCs (HLA-DR dim , CD80 À /CD86 À , IL-10 + /TGF-β + ) Song, Shurin, Tourkova, Chatta, & Shurin, 2004;Teng et al, 2014) by mechanisms dependent on IL-6, IL-8, and VEGF (Cabillic et al, 2006;Figel et al, 2011).…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 99%
“…Interestingly, additional expansion of Tregs was observed in RCC patients in response to IL-2 treatment, which explains the weak efficacy of this therapeutic approach [ 36 ]. Treg induction in RCC can be a consequence of impaired DC activation [ 41 ] and it was shown that other CD4+ cell populations of kidney cancer patients tend to express a naïve/resting phenotype although they do respond to non-specific activation in vitro [ 42 ]. In RCC cases it was shown that circulatory Tregs can differ from their intra-tumoural counterparts, which had increased levels of HLA-DR, Fas, and GITR and simultaneously possessed higher suppressive properties [ 37 ].…”
Section: Immunosuppression In Renal Cell Carcinomamentioning
confidence: 99%